Correlation Between Age, Gender and Bad Oral Habit of 7-9-year-old Children in Karangjati Primary School, Kasihan, Bantul, Yogyakarta - Atiek Driana Rahmawati; Eggi Arguni; Iwa Sutardjo; Dibyo Pramono (Denta Journal Kedokteran Gigi, 2020)
Introduction: Bad oral habit is an intraoral abnormal habit, if it continues until school-age children, it needs more attention because of its effects on craniofacial growth. It can be caused by pathological conditions, anxiety, or psychological disorder. The school-age period is a new environment. Children adjust to some conditions that may cause problems but if they cannot, resulting in psychological tension. Girls have a higher level of anxiety than boys. The boys tend to against the advice of their parents, including stopping doing bad oral habits. Purpose: This study aimed to determine whether there was a correlation between age, gender, and bad oral habit of 7-9-year-old children. Materials and Methods: A cross-sectional study has been done in Karangjati elementary school. The 107 children were examined their oral cavity to observe clinical symptoms that might be lead to bad oral habits. Their parents were asked to fill out the questionnaire to determine whether there were bad oral habits. The data were analyzed by the chi-square. Result: Oral habits were present in 67 from107 children (62.62%) and mostly in 8 years old group (26.17%); more occurred in males (36.45%) than females (26.17%). The highest prevalence was nail-biting (28.97%), followed by lip sucking (23.36%), lip biting (23.36%), thumb/finger sucking (20.5%), bruxism (13.08%) and mouth breathing (8.41%). Chi-square test showed that p-value=0,037 and 0.038 for the correlation between age, gender, and bad oral habit, respectively. Conclusion: There were correlations between age, gender, and bad oral habits of 7-9-year-old children.